2022
DOI: 10.3389/fmed.2021.771313
|View full text |Cite
|
Sign up to set email alerts
|

Dual Burden of Malnutrition Among Adolescents With Hunger Aged 12–15 Years in 41 Countries: Findings From the Global School-Based Student Health Survey

Abstract: Background: Hunger is a pandemic among adolescents, resulting in both underweight and obesity, and posing a substantial health challenge.Objective: To estimate the dual burden of malnutrition among adolescents with hunger.Design: Data were from the Global school-based Student Health Survey (GSHS). In total, data from 26,986 adolescents with hunger across 5 regions and 41 countries between 2010 and 2015 were analyzed in this study. Weighted prevalence and mean estimates of underweight, overweight, and obesity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
2
3
1
Order By: Relevance
“…We also found high obesity prevalence (i.e., 7.4%) among the adolescents, but with substantial discrepancies across countriesconsistent with the results of other studies. 16,21 In contrast to our previous results, 24 our current results indicated that young adolescents experiencing hunger had a relatively high obesity prevalence (8.9%).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We also found high obesity prevalence (i.e., 7.4%) among the adolescents, but with substantial discrepancies across countriesconsistent with the results of other studies. 16,21 In contrast to our previous results, 24 our current results indicated that young adolescents experiencing hunger had a relatively high obesity prevalence (8.9%).…”
Section: Discussioncontrasting
confidence: 99%
“…We also found high obesity prevalence (i.e., 7.4%) among the adolescents, but with substantial discrepancies across countries—consistent with the results of other studies 16,21 . In contrast to our previous results, 24 our current results indicated that young adolescents experiencing hunger had a relatively high obesity prevalence (8.9%). Taken together, these results suggest that both hunger and obesity have become a pandemic among young adolescents and these are serious public health issues globally.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We interestingly found that clustering of frequent soft drink and fast-food consumption, rather than other lifestyle risk clusters, was strongest associated with suicidal attempts in LMICs. It is remarkable that LMICs have greater availability of nutrient-poor and energy-dense foods, the resultant burden of adolescent malnutrition may increase the risk of suicidality in these countries [54].…”
Section: Discussionmentioning
confidence: 99%